PENGARUH MONEY ETHIC PADA PERSEPSI ETIS MAHASISWA AKUNTANSI DENGAN MANACIKA PARISUDHA SEBAGAI VARIABEL PEMODERASI - Partha, Komang Wisnu Arie Guna; Asri Dwija Putri, I Gusti Ayu Made; Bagus Dwirandra, A.A. Ngurah (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.12.TAHUN.2022, 2022)
This research was conducted because of the phenomenon of violations of the professional code of ethics by accountants so that the crisis of public confidence in the accounting profession decreased. The purpose of this study is to examine the effect of money ethics on accounting students' ethical perceptions which will later become the basis for ethical decisions, as well as the use of the manacika parisudha variable which might influence the interaction of money ethics on ethical perspectives. The population in this study is master of accounting students and PPAk students of Udayana University who are still actively participating in lectures per odd semester 2020. The sample selection method uses nonprobability sampling with purposive sampling technique so that 34 accounting students of Udayana University are used as research samples. The data were analyzed using a regression model with the absolute difference method. The regression model has passed the classical assumption test. The results of the first hypothesis show that money ethics has a significant negative effect on ethical perceptions of accounting students, the second result shows that manacika parisudha weakens the influence of money ethics on ethical perceptions of accounting students at Udayana University.